Design and Construction of Automatic Railway Crossing Gate Control Using Proximity and Infrared Sensors Based on Omron CP1E E30-SDRA PLC - Sartono, Kajat; Djamin, Martin; Suryadi, Suryadi (West Science Interdisciplinary Studies, 2024)
Railway crossing gates are one of the railway infrastructure facilities. Currently, there are still many problems, especially in traffic accidents. The cause of traffic accidents at railway crossings generally occurs due to the lack of facilities and infrastructure (rail crossing gates) and negligence of guards in carrying out their duties. Therefore, it is necessary to design an automatic railway crossing gate. The prototype of the automatic railway crossing controller uses proximity and infrared sensors to detect the arrival and departure of trains. When the infrared or proximity sensor detects the arrival of a train, the Programmable Logic Controller (PLC) activates Pulse Width Modulation (PWM), buzzer, and Light Emitting Diode (LED), so that the crossing motor goes down. After the crossing touches the limit switch, the motor stops and the buzzer and Light Emitting Diode (LED) remain on. The infrared or proximity sensor detects the departure of the train so that it reverses the motor so that the crossing goes up, then turns off the buzzer and Light Emitting Diode (LED). In this way, it is hoped that this design can be used to increase the efficiency of the system's operational costs and optimize the railway crossing system and is expected to reduce the number of traffic accidents at railway crossings.